2022
DOI: 10.3389/fphar.2022.866360
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Mechanism of Exercise Preconditioning in Ischemic Stroke

Abstract: Exercise preconditioning has attracted extensive attention to induce endogenous neuroprotection and has become the hotspot in neurotherapy. The training exercise is given multiple times before cerebral ischemia, effectively inducing ischemic tolerance and alleviating secondary brain damage post-stroke. Compared with other preconditioning methods, the main advantages of exercise include easy clinical operation and being readily accepted by patients. However, the specific mechanism behind exercise preconditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 131 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…All these findings showed that the improvement of glymphatic activity after IS could effectively reduce brain edema and promote recovery from motor dysfunction, which explained the connection between glymphatic activity and motor dysfunction. One of the principles of the treatment of IS is to remove harmful metabolites (Zhu et al, 2022). Recent studies have found that voluntary wheel operation accelerated the clearance of glymphatic function and protected mouse synaptic function (He et al, 2017).…”
Section: Relationship Between Damaged Glymphatic System and Motor Dys...mentioning
confidence: 99%
“…All these findings showed that the improvement of glymphatic activity after IS could effectively reduce brain edema and promote recovery from motor dysfunction, which explained the connection between glymphatic activity and motor dysfunction. One of the principles of the treatment of IS is to remove harmful metabolites (Zhu et al, 2022). Recent studies have found that voluntary wheel operation accelerated the clearance of glymphatic function and protected mouse synaptic function (He et al, 2017).…”
Section: Relationship Between Damaged Glymphatic System and Motor Dys...mentioning
confidence: 99%
“…Apoptosis is programmed cell death; its features are cellular swelling, film rupture, and random degradation of DNA ( Zhu et al, 2022 ). There are three kinds of apoptosis pathways, which are the endoplasmic reticulum, receptor, and chondriosome pathways ( Park et al, 2021 ).…”
Section: Mechanisms Of Exercise For Pain Management In Diseasementioning
confidence: 99%
“…When the body is stimulated, oxidative damage to the mitochondria leads to the increased release of pro-apoptotic mediators, which disrupts the oxidation antioxidant balance and leads to the damage of the oxidation organization ( Lushchak et al, 2021 ). Exercise can promote the production of reactive oxygen species in cells, further eliminating them to maintain body homeostasis ( Zhu et al, 2022 ). Meanwhile, long or short-term pretreatment can improve the levels of antioxidant enzymes in the hippocampus and cortex and inhibit some oxidative stress.…”
Section: Mechanisms Of Exercise For Pain Management In Diseasementioning
confidence: 99%
“…Xenobiotic-induced preconditioning in stroke is known as "pharmacological preconditioning," which is referred to as increased tissue tolerance in long-term ischemic injury. 60 It may limit cell death and infarct size and improve organ function. It is an effective neuroprotective method against stroke that can be attained by various agents.…”
Section: Xenobiotic Preconditioningmentioning
confidence: 99%